Molecular phylogeny and characterization of secondary metabolite profile of plant pathogenic Alternaria species isolated from basil. (August 2018) - Siciliano, Ilenia; Franco Ortega, Sara; Gilardi, Giovanna; Bosio, Pietro; Garibaldi, Angelo; Gullino, Maria Lodovica
Abstract: Alternaria leaf-spot is a new disease recently reported on basil in Italy. The correct identification of Alternaria species has suffered from many reclassifications in function of morphological features and molecular data. In our study, we performed an overall approach to obtain a better characterization of basil Alternaria isolates. Morphological characteristics, seven-genome region phylogenic analysis, and secondary metabolite profile differentiated the majority of the isolates as A. alternata. OPA 1–3 and OPA 10–2 were the best molecular regions to discriminate among the isolates. Morphological characteristics and sporulation groups helped to discriminate A. tenuissima from A. alternata isolates. All isolates in the A. sect. Alternaria were mycotoxigenic and pathogenic on basil, the production of mycotoxins was enhanced on basil compared to in vitro conditions used in this work. Highlights: Majority of Alternaria isolates from basil belong to Alternaria sect. Alternaria. Sporulation pattern is able to differentiate A. alternata from A. tenuissima. AOH, AME and TTX were more produced on basil than in vitro. A multidisciplinary approach is useful to identify the species among the section.